Chemical compositions and antimicrobial properties of Piper Sarmentosum – A review - Salwani, Ismail; Mohd Adzim Khalili, Rohin; Mohd Nizam, Zahary (2017)
Herbal medicine has emerged as a popular alternative medicine throughout the world due to the unfavorable report on the side effect of a commercial drug. Alternative treatments from nature product have been brought into investigation due to comprehensive traditional uses, low cost and no harmful effects. Piper sarmentosum Roxb. or kaduk (Piperaceae family) is frequently used in local medicine to treat various diseases and ailments. Traditionally, different parts of P. sarmentosum are widely used as a treatment for fever, coughs, diabetes and joint aches. Different types of phytochemical constituents such tannin, phenolics, sarmentine and sarmentosine have been successfully isolated from parts of P. sarmentosum. Furthermore, the antimicrobial activities of P. sarmentosum against pathogenic microorganisms such Pseudomonas aeroginosa, Methicilin Resistant Staphylococcus aureus (MRSA), Mycobacterium tuberculosis, Aspergillus niger and Candida albicans have been reported before. This review aims to summarize the isolated chemical compositions from the different way of extraction and antimicrobial properties of P. sarmentosum reported from the previous studies.